On Eigenvalues of Hermitian-Adjacency Matrix - Babarinsa, Olayiwola; Mohammad Sofi, Azfi Zaidi; Ibrahim, Mohd Asrul Hery; Kamarulhaili, Hailiza; Bashir, Dlal (Communications in Mathematics and Applications, 2020)
The graph of Hermitian-adjacency matrix is a mixed graph consisting adjacency matrix of an undirected graph and skew-adjacency matrix of a digraph. In this paper we discuss eigenvalues of Hermitian-adjacency matrix. Then we use the eigenvalues to determine the possible Hamiltonian cycles of its graph.